Engagement of the Lateral Habenula in the Association of a Conditioned Stimulus with the Absence of an Unconditioned Stimulus. (15th September 2020) - Choi, Bo-Ryoung; Kim, Dong-Hee; Gallagher, Michela; Han, Jung-Soo
Graphical abstract: Highlights: Increased c-Fos expression in the lateral habenula after unpaired training. More c-Fos–positive signals in the LHb-projecting dopaminergic midbrain of unpaired rats compared with paired rats. LHb-lesioned animals exhibit normal performances in the paired and unpaired training. Abstract: Neurons in the lateral habenula (LHb) are activated by reward omission and inhibited by reward delivery-reward processing functions opposite those of midbrain dopaminergic neurons. To further explore this, we examined the role of the LHb in associating a conditioned stimulus (CS) with the absence of an unconditioned stimulus (US) in an appetitive Pavlovian-conditioning paradigm. Rats underwent training in which a CS (light) was either paired (100% CS–US contingency) or unpaired (0% CS–US contiguity and negative contingency) with an US (food). Rats in the paired group exhibited steady acquisition of conditioned food-cup behaviors, while rats in the unpaired group showed low levels of response throughout training. After training, c-Fos levels were measured in the LHb, substantia nigra pars compacta (SNc), and ventral tegmental area (VTA) of rats in all groups. c-Fos levels were higher in the SNc/VTA of the paired group and the LHb of the unpaired group compared with the group with graded excitatory conditioning due to 50% of the CSs paired with USs and a low rate of USs presented during the intertrial interval and control groups for non-associative factors. The number of c-Fos–positive signals in LHb neurons projecting to dopaminergic midbrain neurons was higher in the unpaired group than in the paired group. Excitotoxic LHb lesions did not affect the acquisition of conditioned behaviors in the association of a CS with the presence or absence of an US. Significant increases in the numbers of c-Fos–positive neurons in the unpaired group suggest that LHb neurons engage in the process that associates a CS with the absence of an US.